Towards a new humanism today (2020)
The essay wants to discuss some aspects concerning the role of human being and its activity in our technological era. Starting from the modern idea of “humanism” it briefly explains Descartes’ and Hobbes’ concepts of subjectivity and shows the limits of them. Then, by referring to Heidegger’s interpretation of Dasein as Mitsein and to Levinas’ category of subject, the essay tries to develop from an ethical viewpoint a relational idea of humanism. This idea can be practically more useful, and ethically more justified, for facing the new challenges of our world, the essay argues.